Improving Students' Listening Skills through Note-taking Exercise Strategies in SMK Muhammadiyah 2 Bontoala - Selvi Selvi; Erwin Akib; Muh. Arief Muhsin (PT ARRUS Intelektual Indonesia, 2024)
This research focuses on efforts to improve students' listening skills through the application of note-taking practice strategies. The focus of this study is to explore how note-taking strategies can help students in understanding and organizing information from listening material delivered orally. The purpose of this study is to find out how effective the note-taking strategy is in improving students' listening skills. This research was carried out using the Classroom Action Research (PTK) approach which was carried out in two cycles. The instrument used in this study is a listening test designed to measure students' listening ability before and after the implementation of note-taking strategies. The results showed a significant improvement in students' listening skills after the implementation of the note-taking strategy. In the first cycle, the average listening score of students increased from 45.00% to 56.00%, while in the second cycle the average score increased further to 66.97%. These findings indicate that note-taking strategies are effective in improving students' ability to absorb and understand information conveyed orally. Thus, this study concludes that note-taking strategies are an effective method to improve students' listening skills and can be implemented in United Kingdom language learning to help students develop better listening skills.